Institutional investors and corporate environmental costs: The roles of investment horizon and investor origin - Wolfgang Drobetz; Sadok El Ghoul; Zhengwei Fu; Omrane Guedhami (European Financial Management, 2023)
Using an international data set that quantifies corporate environmental costs, we analyze the influence of institutional investor ownership, particularly investment horizon and investor origin, on the monetized environmental impact generated by their investee firms. Institutional investor ownership is negatively related to corporate environmental costs. This effect is driven by long-term foreign institutional investors, especially investors from advanced economies. Corporate environmental costs are negatively correlated with firm valuation and positively correlated with the cost of equity. Since corporate environmental costs are not reflected in environmental, social and governance ratings, our results shed new light on the role of institutional investors in shaping corporate environmental impact
Keywords: 650; corporate environmental costs; cost of equity; foreign investors; institutional investors; investment horizon; sustainability